Reserve Bank independence, political responsibility, and the goals of anti-democratic policy: A political 'cri de coeur' in response to an economist's perspective - Gregory, Robert (School of Management Working Papers, 1996)
The paper challenges the argument of VUW Professorial Fellow in Monetary Economics, Dr Ralph Bryant, that 'democratic accountability' is emphasised under the Reserve Bank Act 1989 by a distinction between 'goal independence' and 'instrument independence'. It proposes that the Governorship of the Reserve Bank is an inherently political position, and should be understood as such, but that the terms of the Reserve Bank Act can be seen as part of a more general anti-democratic process of technocratisation based on expectations that aspects of public policymaking can and should be 'insulated' from politics.